2023
DOI: 10.1002/ep.14202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of zinc oxide nanoparticles using peppermint tea (Mentha piperita) dregs extract and their photocatalytic performance

Xue Lin Loh,
Zhong Xian Ooi,
Yi Peng Teoh
et al.

Abstract: Zinc oxide (ZnO) is a n‐type semiconductor with a wide band gap of 3.37 eV and a large excitation binding energy of 60 meV. ZnO nanoparticles (ZnO NPs) is considered as one of the best photocatalyst for the degradation of pollutants in water since it has large surface area to enhance the photocatalytic activity. This article aims to study the feasibility of using the agricultural waste of peppermint tea dregs extract with zinc nitrate hexahydrate as salt precursor to synthesis ZnO NPs through a simple, low cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Rini et al reported a green method of synthesizing ZnO nanoparticles using pineapple-peel extract and evaluated their antibacterial activity [11]. Moreover, almond shells, sugar cane bagasse, eggshells, Viscum album leaves, peppermint tea dregs, marine brown algae, and many plant extracts have been used for the synthesis of ZnO nanoparticles [12][13][14][15]. Hence, the green synthesis approach to obtaining ZnO nanoparticles has significant potential for further exploration and development.…”
Section: Introductionmentioning
confidence: 99%
“…Rini et al reported a green method of synthesizing ZnO nanoparticles using pineapple-peel extract and evaluated their antibacterial activity [11]. Moreover, almond shells, sugar cane bagasse, eggshells, Viscum album leaves, peppermint tea dregs, marine brown algae, and many plant extracts have been used for the synthesis of ZnO nanoparticles [12][13][14][15]. Hence, the green synthesis approach to obtaining ZnO nanoparticles has significant potential for further exploration and development.…”
Section: Introductionmentioning
confidence: 99%